V for vendetta: um diálogo entre quadrinhos e cinema - Oliveira, Cássio de Cerqueira (2016)
This master dissertation aims at elaborating a comparative analysis of the two versions of V for Vendetta (comics and cinema), focusing on the form and strategies of narrative composition used by the authors of the graphic novel, Alan Moore and David Lloyd; and also considering how this narrative has been recomposed into another medium by director James McTeigue in his 2006 film adaptation. To reach this objective we first analyze how some of Alan Moore’s novels have been transposed to the cinema since the beginning of this century, in an attempt to localize the present object of study between the adapted texts and the adaptations. Secondly, we employ theoretical principles by Linda Hutcheon (2011) and Robert Stam (2000, 2008), who define adaptation mainly in terms of transposition from other media (as comics and literature) into the cinema. Finally, we describe how the printed version used some resources of comics (images and words) to compose the narrative of V for Vendetta (1988-1989), and how the homonymous film by James McTeigue (2006) recreates similar aesthetics effects, while also being